Inequality in the Human Rights of Mothers and Children in Law Number 23 of 2002 concerning Child Protection Violates the Fifth Principle of Pancasila - Saly, Jeane Neltje; Beale, Aurelius Steven; Effendi, Kevin Noble; Simarmata, Michael Kalep; Wafi, Auzan; Ferdinandus, Nathanael; Sulistiawan, Arya (CV. Rayyan Dwi Bharata, 2023)
Pancasila as a value that is aspired to and used as the ideology of the nation and state and becomes the basis of laws and regulations in Indonesia. One of the development sectors guaranteed by Pancasila is development in the field of social welfare. The fifth precept of Pancasila contains the right of every citizen to have freedom of property rights, social security rights, the right to get a job and health protection. However, there are still inequalities in the right to health and education rights received by children. Child and maternal deaths and many children who drop out of school and some rural school children have not enjoyed the facilities and infrastructure of the government. The research method used is the normative juridical method. The research approach uses the statutory approach method (statute approach), concept approach (conceptual approach) and case approach (case approach). The realization of human rights in accordance with the fifth principle of Pancasila is maintaining a balance between rights and obligations, respecting the rights of other people, respecting the rights of other people including the right to education and the right to health of children. The implementation of SJJN and the APBN budget for education is an embodiment of the Pancasila values from the fifth principle so that children no longer experience inequality in their health and education rights. Legal protection for mothers and children for unequal rights based on Law Number 23 of 2002 concerning Child Protection, which includes unequal health rights and educational rights received by children and mothers. In overcoming inequality of rights, the government should optimize the implementation of UUPA regulations regarding maternal child health and the right to education.